Evaluasi Pembelajaran Pendidikan Agama Islam Berbasis Ranah Afektif - Ahmad Rasyid Ridho; Nur Ayu Setyariza; Sri Erna Widayati; Intan Kusuma Wardani; Yekti Handayani (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Islamic Religious Education (PAI) is a process of transferring knowledge, understanding, values ​​and practicing Islamic teachings in a planned, systematic and sustainable manner. In other words, PAI is an effort to develop the natural instinct of students that has been brought since birth into an ability and strength that can produce professional competence. On the one hand, natural instinct can be interpreted as a tendency (potential) to know, understand and practice Islamic teachings both as servants of Allah and as caliphs of Allah on earth. To develop this natural instinct, PAI must be able to direct and guide students in accordance with Islamic teachings. One thing that is very urgent in the implementation of PAI is that it must be based on the instillation of Islamic morals by emphasizing the instillation and habituation of moral action in the lives of students. This is based on the assumption that the essence of Islamic teachings is the practice and practice of akhlaq al-karîmah.